Heterologous expression of the yeast HAL5 gene in tomato enhances salt tolerance by reducing shoot Na+ accumulation in the long term. Issue 4 (12th June 2014) - García‐Abellan, Jose O.; Egea, Isabel; Pineda, Benito; Sanchez‐Bel, Paloma; Belver, Andres; Garcia‐Sogo, Begoña; Flores, Francisco B.; Atares, Alejandro; Moreno, Vicente; Bolarin, Maria C.
<x xml:space="preserve">Abstract</x> For salt tolerance to be achieved in the long‐term plants must regulate Na+/K+ homeostasis over time. In this study, we show that the salt tolerance induced by overexpression of the yeast HAL5 gene in tomato (Solanum lycopersicum) was related to a lower leaf Na+ accumulation in the long term, by reducing Na+ transport from root to shoot over time regardless of the severity of salt stress. Furthermore, maintaining Na+/K+ homeostasis over time was associated with changes in the transcript levels of the Na+ and K+ transporters such as SlHKT1;2 and SlHAK5. The expression of SlHKT1;2 was upregulated in response to salinity in roots of transgenic plants but downregulated in the roots of wild‐type (WT) plants, which seems to be related to the lower Na+ transport rate from root to shoot in transgenic plants. The expression of the SlHAK5 increased in roots and leaves of both WT and transgenic plants under salinity. However, this increase was much higher in the leaves of transgenic plants than in those of WT plants, which may be associated with the ability of transgenic leaves to maintain Na+/K+ homeostasis over time. Taken together, the results show that the salt tolerance mechanism induced by HAL5 overexpression in tomato is related to the appropriate regulation of ion transport from root to shoot and maintenance of the leaf Na+/K+ homeostasis through modulation of SlHKT1 and SlHAK5 over time.